Continuity of drag and domain stability in the low mach number limits - Feireisl, Eduard; Friedmann, Elfriede (Journal of mathematical fluid mechanics, 2012)
We consider a mathematical model of a rigid body immersed in a viscous, compressible fluid moving with a velocity prescribed on the boundary of a large channel containing the body. We assume that the Mach number is proportional to a small parameter ε and that the general boundary of the body contains small asperities of amplitude proportional to ε α for a certain α > 0 and suppose the Navier’s slip condition on this rough boundary.
First online: 29 August 2012
Gesehen am 14.06.2018